Functional and radiological outcome after closed reduction and percutaneous pinning versus open reduction and internal fixation in displaced supracondylar fractures in children - Amin Kumar Shrestha; Suresh Uprety; Govinda K.C.; Sharma Paudel (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Supracondylar fracture of humerus is very common fracture in pediatric age group. The current trends of management in displaced type are close reduction and per cutaneous pinning (CRPP), if reduction is not satisfactory then open reduction and internal fixation (ORIF) is done.  Our study aims to compare the cosmetic, functional and radiological outcome between these two methods.